Build and Test Research of a Coaxial Hybrid-power Gas Engine Heat Pump System Based on LiFePO4 Battery. (2016) - Ji, Wenxiu; Cai, Liang; Men, Qinkun; Sun, Gaofeng; Zhang, Xiaosong
Abstract: Power batteries of hybrid-power gas engine heat pump (HPGHP) often encounter frequent charge and discharge operations, which have an adverse effect on nature gas conversion efficiency of system. In order to improve the dynamic efficiency and economic performance of HPGHP, this paper raises a coaxial HPGHP facility, which takes the LiFePO4 battery as the auxiliary power source to drive the compressor. Logic threshold control strategy is put forward to distribute power between the gas engine and battery pack. Test research was operated to verify the advantageous performance of LiFePO4 battery HPGHP. The results show that LiFePO4 battery HPGHP can achieve an obvious energy saving effect, especially in low-load condition and high-load condition. When compressor speed increases from700rpm to 2500rpm, COP decreases from 4.76 to 3.25, heating capacity increases from 14.52 to 33.13kW. The maximum difference of LiFePO4 battery HPGHP and lead-acid battery HPGHP is respectively 13.2%, 11.28% and 10.2% separately for engine thermal efficiency, gas-consumed rate, and energy conversion efficiency under the same load. In addition, reclaimed heat is tested and the result shows that LiFePO4 battery HPGHP is 11.82% lower than conventional nature gas heat pump (GHP).